An International Comparison of the Volatility of Strike Behavior - Cameron, Samuel (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
This paper develops a synthetic mode! of the strike process which suggests the use of volatility as the measure of severity rather than levels or regression intercepts